Pengaruh Gaya Kepemimpinan, Kompensasi Dan Kompetensi Terhadap Kinerja Kerja Guru Madrasah Aliyah Negeri (MAN I Malang) - Ida Fitriana; Abdul Qodir Djaelani; Muhammad Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACTThe purpose of this study is to determine whether is a relationship between leadership, compensation and competence of teacher performance MAN I Malang. The population taken for this study is the performance of MAN I Malang teachers who numbered 63 people. The sample method because in the population there are various levels of position also there are various levels of this study is a questionnaire. The data collected ther processed techriques with the help of SPSS software (Statistical Package for Social).Result indicates that leadership, competency and compensation are significantly influence teacher performance. The correlation of leadership with teacher performance is 0,455. The correlation between compensation and staff performance is 0,335. And the last, the correlation between competency and teacher performance is 0,227. It is also shown that leadership, compensation and competency can explain teacher performance variation as much as 1, 017.Key words: leadership, compensation, competency, performance.